An Islamic Economic Perspective on the Partnership Model of Broiler Chicken Farmers in Pematang Rahim Village, Mendahara Ulu - Saiful Huda; Wargo; Kurniawan (Zabags International Journal of Islamic Studies, 2025)
The increasing demand for animal protein in Indonesia has driven the growth of the broiler chicken farming sector, including in Pematang Rahim Village, Mendahara Ulu, which exhibits diverse partnership dynamics between farmers and business partners. This study aims to identify the partnership models adopted by broiler chicken farmers in the region and evaluate their alignment with Islamic economic principles. Employing a qualitative descriptive approach with a case study strategy, data were collected through in-depth interviews, field observations, and documentation involving farmers partnered with both corporate entities and individual brokers. The findings reveal that formal structures, written contracts, provision of production inputs, and technical guidance characterize corporate partnerships. In contrast, individual partnerships are informal, flexible, and lack oversight and equitable risk-sharing mechanisms. From an Islamic economic perspective, corporate partnerships resemble syirkah principles, while individual partnerships reflect mudharabah practices with notable deviations from fairness and transparency. This study contributes conceptually to the development of partnership models based on maqashid sharia, emphasizing justice, sustainability, and public welfare. The implications of these findings are relevant for policymakers, practitioners, and Islamic financial institutions in designing livestock partnerships that are locally adaptive and aligned with Islamic values.